2019
DOI: 10.18632/aging.102323
|View full text |Cite
|
Sign up to set email alerts
|

Gomisin M2 from Baizuan suppresses breast cancer stem cell proliferation in a zebrafish xenograft model

Abstract: Gomisin M2 isolated from Schisandra viridis A. C. Smith has potential anti-tumor effects on certain cancers, including breast cancer. However, only a few investigations have been conducted on the effects of Gomisin M2 on breast cancer stem cells (CSCs), which have the ability to self-renew and differentiate, as a possible strategy to resolve cancer cell resistance to apoptosis and to improve treatments. It is essential to investigate the effects of Gomisin M2 on breast cancer stem cells (BCSCs). In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Moreover, S. chinensis has been certified as a safe nutritional ingredient by the European Food Safety Agency, and its fruit has been reported to have diverse pharmacological properties, including antioxidant, anti-inflammatory and antiallergic effects (17,40). GM2 extracted from S. chinensis has also been documented to exert various pharmacological effects, including preventing liver damage and reducing cancer cell proliferation (18,19,41). Based on these benefits, the present study explored the inhibitory effects of GM2 on IMQ-induced psoriasis-like skin inflammation and on TNF-α-and IFN-γ-stimulated keratinocytes after the purity of the GM2 isolated from S. chinensis was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S. chinensis has been certified as a safe nutritional ingredient by the European Food Safety Agency, and its fruit has been reported to have diverse pharmacological properties, including antioxidant, anti-inflammatory and antiallergic effects (17,40). GM2 extracted from S. chinensis has also been documented to exert various pharmacological effects, including preventing liver damage and reducing cancer cell proliferation (18,19,41). Based on these benefits, the present study explored the inhibitory effects of GM2 on IMQ-induced psoriasis-like skin inflammation and on TNF-α-and IFN-γ-stimulated keratinocytes after the purity of the GM2 isolated from S. chinensis was determined.…”
Section: Discussionmentioning
confidence: 99%
“…A highly potent small-molecule inhibitor CWP232228 can preferentially inhibit bCSC proliferation via antagonizing the binding of β-catenin to T-cell factor (TCF) in the nucleus ( 246 ). Another natural product, gomisin M2, downregulates Wnt/β-catenin signaling and inhibits bCSC proliferation, mammosphere formation, and self-renewal ( 247 ). Studies indicate multiple interaction points or crosstalk between Notch and Wnt/β-catenin signaling pathways, and thus it is essential to focus on Notch-Wnt synergies in BC progression ( 248 ).…”
Section: Mechanisms and Approaches To Overcome Multimodal Drug Resist...mentioning
confidence: 99%
“…A previous study has shown that Wnt/β-catenin signaling pathway was deemed as a key mechanism of Sam68- mediated self-renewal in BC cells ( Wang L. et al, 2015 ). Another study displayed that Gomisin M2 remarkably inhibited BCSCs self-renewal by suppressing the Wnt/β-catenin signaling pathway ( Yang Y. et al, 2019 ). Compared to other cells, the higher level of Wnt/β-catenin signaling pathway contributes to the high resistance level of BCSC.…”
Section: Central Signaling Pathways In Breast Cancer Stem Cellsmentioning
confidence: 99%